The Influence of Digital Promotion Strategies on Consumer Purchase Intentions for Culinary Products at Kampoeng Lauk Palangka Raya - Noorjaya Nahan; Aston Pakpahan; Muhamad Ruzaini Abdi (SEULANGA SYSTEM PUBLISHER, 2025)
The increasing reliance on digital media has transformed how consumers search for information, evaluate products, and make purchase decisions, especially in the food and beverage industry. Local culinary businesses must now adapt to a digital environment where effective promotional strategies can determine their competitiveness and sustainability. In response to this shift, this study examines the effectiveness of digital promotion strategies in influencing consumer purchase intention, with Kampoeng Lauk Palangka Raya serving as the case study. A quantitative approach was employed by distributing structured questionnaires to consumers exposed to Kampoeng Lauk's digital marketing efforts through social media and online platforms. Multiple linear regression analysis assessed the influence of various digital strategies, including social media content, endorsements, and paid advertisements, on consumer behavior. The results indicate that digital promotion strategies have a statistically significant impact on purchase intention. Among the variables, informative and engaging social media content was the most influential factor in motivating consumers to consider purchasing. These findings emphasize the importance of using digital tools strategically to build customer interest and brand loyalty. The study recommends that small and medium-sized culinary enterprises (SMEs) develop creative, audience-tailored content and utilize digital analytics to refine their marketing efforts. Ultimately, this research contributes to the growing discourse on digital marketing in the local business context and provides actionable insights for culinary entrepreneurs aiming to compete in a dynamic digital marketplace.